The Current Status and Influencing Factors of Digital Product Use Among Young Children in the Digital Age - Li, Jixia; Agvaantseren, Uranchimeg; Qin, Li (Journal of Ecohumanism, 2024)
The rapid development of digital technology has fundamentally changed family education in the digital age. This study aims to explore the current status of digital product use and influencing factors among children aged 0-6 years. This study examined the prevalence of digital devices, average screen time, and parents' attitudes toward digital technology in early childhood education by conducting a questionnaire survey of 1,477 families in Sichuan Province , China, and in-depth interviews with four families. The results show that digital products are widely present in families and parents recognize their educational value, but also face challenges in content, time, and online safety management. Differences in parents' digital literacy levels further affect their ability to support children's digital activities. This study recommends the development of a comprehensive parent education program, the establishment of a high-quality digital resource platform, and the strengthening of family guidance to optimize the use of digital technology in early childhood education. The findings contribute to the global discussion on digital literacy, early childhood development, and family education.